Cancel Culture Sebagai Bentuk Kontrol Sosial di Twitter - Deni Yanuar; Nadia Muharman; Mhd Yudha Teguh Pratama Yudha; Rahmawati Rahmawati; Nur Anisah Anisah; Maini Sartika Maini (Jurnal Media dan Komunikasi, 2023)
ABSTRACT The cancel culture movement has become popular since the hashtags #MeToo and #BlackLivesMatter were buzzing on Twitter about justice for victims of sexual harassment and human rights against the black race in the United States. In this study, the researcher took a case study on the refusal of Saiful Jamil to return to appear on television as part of the cancel culture phenomenon that occurred in Indonesia. The cancel culture aimed at Saiful Jamil is a consequence he has to get because of the excessive glorification of himself after being released from prison. This study aims to find a relationship that cancel culture is an effort to control social as a form of social control on social media. The subject of this research is public tweets related to the rejection of Saiful Jamil. In this study, the object of research is the cancel culture that occurred to Saiful Jamil. The conclusion in this study is that the cancel culture carried out by the community against Saiful Jamil is a form of social control that is carried out through education, reprimand, and sanctions as a consequence of the deviations he commits. Keywords : cancel culture, social control, sanction, twitter.